A description of the most frequent speaking activities implemented by teachers in advanced English I courses at Foreign Language Department in Bachelor of arts major emphasis in English teaching semester II,2016 - Cruz Chanta, Karla Guadalupe; García Menjivar, Jeremías Joel; Mejía Teas, Denis Alexander (2024)
This research group intends to find out the most frequent speaking activities implemented by teachers in Advanced English I courses at Foreign Language Department in bachelor of arts major emphasis in English teaching semester II, 2016. For this research, as a group will take into account the speaking activities such as debate, oral presentation, brainstorming, role-play, reading and discussing the material in class, speak task, making video, discussing that teachers apply at the moment to impart the class for encourage their students some oral activities, in the group opinion, can help to overcome difficulties when using this speaking activities. In the first chapter, the team will expose the interest of this research. Also, they will present the sample of students this research has been based upon. In the second chapter, the researchers begin with a theoretical framework. The third chapter presents the methodology of the project and the group team report the events of the implementation of a number of speaking activities that can help overcome the problems students may find when speak English. The investigators will present the analysis of the observation in chapter four. Finally, as a group will expose our conclusions and recommendations of this research project.